2015
DOI: 10.3928/01477447-20150204-05
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Transarticular K-wire Fixation of Critical Ankle Injuries at Risk: A Neglected “Damage Control” Strategy?

Abstract: High-energy ankle fracture-dislocations are at significant risk for postoperative complications. Closed reduction and temporary percutaneous transarticular K-wire fixation was first described more than 50 years ago. This simple and effective "damage control" strategy is widely practiced in Europe, yet appears largely forgotten and abandoned in the United States. Anecdotal opposing arguments include the notion that drilling K-wires through articular cartilage may damage the joint and contribute to postinjury ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…The subjective outcome scores at a median follow-up period of 2 years using the Foot and Ankle Outcome Score questionnaire found that most patients recovered well. 10 These findings support that the 2.0-mm-diameter drill holes placed through the subtalar joints may not induce the clinically relevant articular damage that can manifest in secondary postinjury arthritis development. Given the nature of these generally high-energy intra-articular injuries and will be impossible to know if the additional join damage from a few small pin penetrations can have a long-term impact on the fate of the joint.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The subjective outcome scores at a median follow-up period of 2 years using the Foot and Ankle Outcome Score questionnaire found that most patients recovered well. 10 These findings support that the 2.0-mm-diameter drill holes placed through the subtalar joints may not induce the clinically relevant articular damage that can manifest in secondary postinjury arthritis development. Given the nature of these generally high-energy intra-articular injuries and will be impossible to know if the additional join damage from a few small pin penetrations can have a long-term impact on the fate of the joint.…”
Section: Discussionsupporting
confidence: 66%
“…A considerable concern is that the penetrating K-wire could damage the subtalar joint surface and accelerate the onset of subtalar arthritis. Friedman et al 10 reported the clinical results of temporary transarticular ankle pin fixation in critical ankle injuries. The subjective outcome scores at a median follow-up period of 2 years using the Foot and Ankle Outcome Score questionnaire found that most patients recovered well.…”
Section: Discussionmentioning
confidence: 99%
“…But the results support that already during initial fracture stabilization with an AEF, the option of prolonged or final treatment with an EF should be considered in polymorbid geriatric patients [11,12,18]. Depending on the soft tissue situation and the fracture morphology, additional less invasive osteosyntheses should be considered [7,19,20]. There is no uniform approach to additive procedures either in the current literature or in our institution, which reflects a limitation of the present study.…”
Section: Discussionmentioning
confidence: 52%
“…On the one hand, additional procedures may be temporary and will be removed during conversion to ORIF or at the time of EF removal after fracture healing, e.g., temporary retrograde calcaneotalotibial K-wire stabilization. It could be shown that temporary retrograde calcaneotalotibial K-wire stabilization is not an obvious trigger for osteoarthritis in this patient group [19,20]. Without additional external stabilization, good radiological results are only achieved in 33% [12].…”
Section: Discussionmentioning
confidence: 77%
“…To prevent pin site infection, cleansing with hydrogen peroxide, chlorhexidine gluconate (CHG), or saline appears safe and beneficial [12]. In addition to external fixation, percutaneous fixation using Kirschner wires or screws have been shown to be valuable adjuncts in temporary management of fractures and dislocations of both upper and lower extremity injuries [13].…”
Section: Temporary Stabilizationmentioning
confidence: 99%